2011
DOI: 10.1007/s00198-011-1535-z
|View full text |Cite
|
Sign up to set email alerts
|

GRAND: the German retrospective cohort analysis on compliance and persistence and the associated risk of fractures in osteoporotic women treated with oral bisphosphonates

Abstract: Compliance and persistence with oral bisphosphonates in German women with osteoporosis were inadequate. Better compliance and persistence can prevent fractures in these women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
2
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 41 publications
7
78
2
6
Order By: Relevance
“…Adherence of this level is commonly observed in clinical trials, likely due to patients in clinical trials being motivated and receiving regular reminders from the investigators to take their medication [25][26][27]. However, compliance with therapy for osteoporosis in clinical practice, as with other chronic disorders, is often low [4,7]. Indeed, reviews of prescription claim databases evaluating patients not included in clinical trials suggest that compliance with bisphosphonate therapy is in the range of 37-52% [9,28,29], and persistence rates at month 12 have been shown to be around 30-57% [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Adherence of this level is commonly observed in clinical trials, likely due to patients in clinical trials being motivated and receiving regular reminders from the investigators to take their medication [25][26][27]. However, compliance with therapy for osteoporosis in clinical practice, as with other chronic disorders, is often low [4,7]. Indeed, reviews of prescription claim databases evaluating patients not included in clinical trials suggest that compliance with bisphosphonate therapy is in the range of 37-52% [9,28,29], and persistence rates at month 12 have been shown to be around 30-57% [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a recent retrospective analysis of more than 4,000 patients receiving oral bisphosphonates showed that overall compliance was poor, with only 51% of patients considered compliant. Patients receiving daily oral bisphosphonate therapy had particularly poor compliance [7]. Compliance has been shown to be improved with reduced frequency of dosing (monthly versus weekly or daily bisphosphonate therapy); nevertheless, compliance remained suboptimal in patients receiving less frequent dosing [28,31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Наши данные по привержен-ности в течение года соответствуют показателям настой-чивости пациентов в лечении этим препаратом, полу-ченным в четырех странах Европы (Германия, Австрия, Греция и Бельгия), которая составила 87-95,3% [13]. При этом настойчивость в лечении (как в нашей работе, так и в европейских странах) была в 1,5-10 раз выше, чем у больных, получавших бисфосфонаты (7,2-58%) [14,15]. В то же время в работе, представленной автора-ми из Германии, которые оценивали приверженность ле-чению ДС и различными бисфосфонатами в течение 2 лет у 45 592 больных, были выявлены более низкие показа-тели приверженности [16].…”
Section: результатыunclassified